Building or Bypassing Recipient Country Systems : Are Donors Defying the Paris Declaration? - Knack, Stephen (Taylor and Francis, 2014)
The 2005 Paris Declaration committed donors to increased use of recipient country systems for managing aid, particularly in countries with higher-quality systems. Using indicators explicitly endorsed by the Paris Declaration and covering the 2005-2010 period, this study finds a positive, significant, and robust relationship between quality of systems and their use by donors. Thus, donors appear to have modified at least some of their aid practices in ways that build rather than undermine administrative capacity and accountability mechanisms in recipient countries. However, quality of systems explains a relatively small share of the variation in their use, and there is considerable heterogeneity among donors in their use of country systems, and in their sensitivity to quality of systems.